Loading...

= 53 9x3 + 9x2 + 5x1+ 3x1 27 + 18 + 5 + 3

If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)

9x3=27.

7 + ( 9 x ( 3 - 1 ) ) = 25

yes

This is non-linear

(3x + 5)(3x^2 + 4)

(3x2 + 2x + 1)

9x(x2+3x-10) * * * * * 9x3 + 27x2 - 90x = 9x(x2 + 3x - 10) = 9x(x + 5)(x - 2).

Divide both terms by 24. 24(9x3 +1)

9*3=27 8*22=176 27 + 7 + 176=210

10

2048

3 x 9 = 27

42

4+1=5. Plus 4 equals 9. Plus 77685769844446473 equals 77685769844446482. Plus 3 equals 77685769844446485. Plus 8 equals 77685769844446493. Plus 1 equals 77685769844446494. Plus 9870998342523322424 equals 1064785604097768918. Plus 4 equals 1064785604097768922.

3

(x + 2)(3x - 1)(3x + 1)

9x3 is also 9+9+9. 9x3 = 27

the answer is a

No.

89

If I am correct, 9 plus 7 equals 112.

1 plus 19 equals 20 2 plus 18 equals 20 3 plus 17 equals 20 4 plus 16 equals 20 5 plus 15 equals 20 6 plus 14 equals 20 7 plus 13 equals 20 8 plus 12 equals 20 9 plus 11 equals 20 10 plus 10 equals 20 1 times 20 equals 20 2 times 10 equals 20 4 times 5 equals 20

20 plus 49 equals 69